Features of the Hospital Course Myocardial Infarction in Patients with Disorders of Carbohydrate Metabolism (Eurasian Medical Research Periodical, 2022)
To study the clinical course of acute myocardial infarction (MI) with ST segment elevation and features of inpatient treatment in patients with diabetes mellitus diabetes and without it. Material and methods: 83 patients admitted to hospital in 2014 were included. Patients were divided into two groups depending on the presence or absence of carbohydrate metabolism disorders: group 1 (patients with type 2 diabetes; n=38) and group 2 (patients without carbohydrate metabolism disorders; n=45). We studied the initial clinical, demographic and laboratory-instrumental characteristics of patients, as well as the features of inpatient treatment. Results: In group 1, compared with group 2, arterial hypertension was significantly more often recorded (73.7% vs. 49%; p